Legislative Responses to Terrorism: A Critical Review of Counterterrorism Measures - Rodiyah, Rodiyah; Amandha, Asyaffa Ridzqi; Utari, Indah Sri; Nte, Ngboawaji Daniel (Indonesian Journal of Counter Terrorism and National Security, 2023)
In the face of escalating global terrorism threats, nations worldwide have grappled with the imperative to enact and amend legislation aimed at preventing, detecting, and prosecuting acts of terrorism. This paper conducts a comprehensive and critical examination of legislative responses to terrorism, with a focus on their efficacy, implications for civil liberties, and broader societal impacts. The research begins by analysing the evolution of counterterrorism laws across diverse jurisdictions, emphasizing the shifting landscape of security concerns and the subsequent legal adjustments. It scrutinizes the core features of these legislative measures, including preventive detention, surveillance, intelligence gathering, and the definition of terrorism offenses. A critical analysis is employed to assess the balance between security imperatives and the protection of individual liberties, scrutinizing the potential for abuse, discrimination, and erosion of due process. Case studies from various countries illuminate the real-world consequences of counterterrorism legislation, shedding light on the impact on marginalized communities, legal frameworks, and international human rights standards. The paper also explores the effectiveness of oversight mechanisms, judicial review, and safeguards incorporated within these legislative frameworks to curb potential abuses and protect against overreach. Furthermore, the study considers the role of technology, intelligence-sharing agreements, and international cooperation in shaping legislative responses to terrorism. It aims to provide a nuanced understanding of the challenges and successes in addressing the complex interplay between security concerns and the preservation of fundamental rights. This critical review seeks to contribute to the ongoing dialogue on counterterrorism policy by offering insights into the multifaceted implications of legislative responses. The paper concludes with recommendations for fostering a balanced approach that upholds both security imperatives and the foundational principles of democracy.